Characterization of non-cytosolic hexokinase activity in white skeletal muscle from goldfish (Carassius auratus L.) and the effect of cold acclimation. Issue 6 (27th September 2010) - dos Santos, Reinaldo Sousa; Diniz, Luan Pereira; Galina, Antonio; da-Silva, Wagner Seixas
Abstract : HK (hexokinase) is an enzyme involved in the first step in the glucose metabolism pathway, converting glucose into G6P (glucose 6-phosphate). Owing to the importance of skeletal muscle for fish swimming and acclimation processes, we used goldfish ( Carassius auratus L.) white muscle in order to investigate subcellular distribution and kinetics of HK. In this study, we report that HK activity is predominantly localized in the mitochondrial fraction [NC-HK (non-cytosolic HK)] in goldfish white muscle. Studies of the kinetic parameters revealed that the K m (Michaelis–Menten constant) for glucose was 0.41±0.03 mM and that for mannose was 3-fold lower, whereas the affinity for fructose was too low to be measured. The K m for ATP was 0.88±0.05 mM, whereas no activity was observed when either GTP or ITP was used as a phosphate donor. A moderate inhibition (20–40%) was found for ADP and AMP. Similar to mammalian HK, G6P and glucose analogues were able to promote an inhibition of between 85 and 100% of activity. Here, we found that acclimation of goldfish at 5°C promoted a 2.5-fold increase in NC-HK compared with its counterpart acclimated at 25°C. However, cytosolic HK activity was not altered after thermal acclimation. In summary, our results suggest that the goldfish has a constitutive NC-HK that shows some similarities to mammalian HK-II and, curiously, may play a role in the broad metabolic changes required during the cold acclimation process.